1980
DOI: 10.1192/bjp.136.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Special Hospital Patients to the NHS

Abstract: In 1976, 163 patients were approved by the Department of Health and Social Security for transfer from the Special Hospitals to the open wards of the National Health Service. By autumn 1978, a quarter were still waiting for admission. Patients meeting most difficulty were the severely handicapped non-offenders, who were usually refused unseen on the ground that local subnormality hospitals were full. The role of the DHSS and of the Regional and Area Authorities was in general restricted to bewailing problems th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…A review of the medium to long term outcomes of discharges from HSPHs in E&W, with follow up between 2-11 years, suggests that hospital readmission rates range between 7 - 22% [19]. Reconviction studies of released HSPH patients also suggest that the rate of serious reconvictions ranges from 3% to 24% overall, [20-22]. However, Davison et al [23] reported that rates were notably higher in patients with a diagnosis of Axis II personality disorder rather than an Axis I disorder.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the medium to long term outcomes of discharges from HSPHs in E&W, with follow up between 2-11 years, suggests that hospital readmission rates range between 7 - 22% [19]. Reconviction studies of released HSPH patients also suggest that the rate of serious reconvictions ranges from 3% to 24% overall, [20-22]. However, Davison et al [23] reported that rates were notably higher in patients with a diagnosis of Axis II personality disorder rather than an Axis I disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Bowden (1981) reported in a review of studies of discharges from high security with followup between 2-11 years that readmission rates ranged between 7%-22%. Studies reporting on re-offending behaviour suggest that the rate of serious reconvictions ranges between 3% to 30% (Black and Spinks, 1977;Dell, 1980;Tennent and Way, 1984;Bailey and MacCulloch, 1992), but Davison et al (1999) noted that rates were notably higher in patients previously detained under the legal category of psychopathic disorder (PD).…”
Section: Introductionmentioning
confidence: 99%
“…This, as Susanne Dell (1980) has shown, has to an important extent been due to a hardening of the attitudes of the psychiatric services to Special Hospital patients. The present study demonstrates that Broadmoor's patients are now staying longer in conditions of maximum security than their pre decessors, and it is the firm opinion of Broadmoor con sultants that this is unjustifiable on clinical grounds.…”
Section: Resultsmentioning
confidence: 99%